A Conceptual Review of Automobile Disc Brake Friction Materials - Mawuli, Seckley Emmanuel; Anthony, Simons; Akintunde, Dahunsi Olurotimi (European Journal of Applied Sciences, 2022)
Providing an alternative filler material for brake pads is crucial because the use of asbestos as filler material in brake pads has some health risks. It is known that asbestos can cause Asbestosis and Mesothelioma. This has, therefore, ignited widespread research into development and finding of eco-friendly brake friction organic materials. In this paper, some works done by various researchers in a bid to finding suitable environmentally friendly and best performed compositions for brake friction materials have been presented. The use of natural fibres such as maize husks, coconut shell, palm kernel shell, cocoa beans shell, bagasse, periwinkle shell, sawdust and banana peels as reinforcement to replace asbestos in the production of brake friction materials with high mechanical properties, stable friction, high wear resistance, lightweight, low environmental impact and low cost have been presented. This extensive survey, however, shows that there is no research on the suitability of other materials such as other types of periwinkle shells, coconut shell ash and kaolin to replace asbestos as major ingredients in a brake friction material. There is, therefore, the need to continue to research into and develop low-cost non asbestos organic brake pad materials for better brake performance.